2010
DOI: 10.1021/tx900414g
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450-Mediated Epoxidation of 2-Aminothiazole-Based AKT Inhibitors: Identification of Novel GSH Adducts and Reduction of Metabolic Activation through Structural Changes Guided by in Silico and in Vitro Screening

Abstract: A 2-aminothiazole derivative 1 was developed as a potential inhibitor of the oncology target AKT, a serine/threonine kinase. When incubated in rat and human liver microsomes in the presence of NADPH, 1 underwent significant metabolic activation on its 2-aminothiazole ring, leading to substantial covalent protein binding. Upon addition of glutathione, covalent binding was reduced significantly, and multiple glutathione adducts were detected. Novel metabolites from the in vitro incubates were characterized by LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Such mechanisms would be consistent with those proposed for other thiazolecontaining compounds (Obach et al, 2008;Sevrioukova and Poulos, 2010;Subramanian et al, 2010;Rock et al, 2014). The chloro-ethyl side chain of CMZ may also be involved in the enzyme inactivation described here.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Such mechanisms would be consistent with those proposed for other thiazolecontaining compounds (Obach et al, 2008;Sevrioukova and Poulos, 2010;Subramanian et al, 2010;Rock et al, 2014). The chloro-ethyl side chain of CMZ may also be involved in the enzyme inactivation described here.…”
Section: Introductionsupporting
confidence: 90%
“…A noncovalent, metabolic intermediate complex could also form after NADPH-dependent conversion to a tight-binding metabolite(s). It is interesting to note that CMZ contains a thiazole functional group in common with potent CYP3A4 inhibitors cobicistat and ritonavir and compounds known to undergo metabolic activation and covalent binding to microsomal protein, including ritonavir, sudoxicam, meloxicam, and a series of AKT inhibitors (Obach et al, 2008;Subramanian et al, 2010;Rock et al, 2014). It has been postulated that initial events leading to metabolic activation of the thiazole and subsequent covalent binding are epoxidation of the C4-5 bond (Subramanian et al, 2010) or sulfoxidation (Rock et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, two studies have reported that cytochrome P450s can catalyze the bioactivation of thiazole rings to intermediates that form covalent bonds to protein (Subramanian et al, 2010;Obach et al, 2008) via the formation of an epoxide intermediate. The structures of the GSH adducts to bioactivated thiazoles (e.g., sudoxicam, meloxicam, and multiple 2-aminothiazole derivatives) have been determined.…”
Section: Discussionmentioning
confidence: 99%
“…11) Compound 69 exhibited 64% oral bioavailability with respectable plasma drug exposure (auc = 2600 ng·h/mL, 5 mg/kg) and longer half-life (t 1/2 = 4.3 h). All of these compounds were cleared via oxidation of the thiazole ring [87], therefore their half-lives were similar. In vivo pharmacodynamic (PD) studies in mice six hours after a 30 mg/kg dose, plasma concentration of 69 was about 10-fold over its cellular IC 50 , and significant inhibition of PRAS40 phosphorylation was observed (43%).…”
Section: Substituted-azole Derivativesmentioning
confidence: 98%